Curating research occasional table - O'Neill, Paul 1970-; Wilson, Mick (Occasional table, 2015)
An opening to curatorial enquiry : introduction to curating and research Paul O'Neill & Mick Wilson -- The complete curator Liam Gillick -- Towards the exhibition as research Simon Sheikh -- Renewing the curatorial refrain : sustainable research in contemporary art Maja & Reuben Fowkes -- And the question is Georgina Jackson -- Academy as exhibition Henk Slager -- What if an institution was curated? Intermediae as an institutional hypothesis Olga Fernandez Lopez -- Post-research notes : (re)search for the true self-managed art Jelena Vesić -- Movements that matter : the Projekt Migration (2003-06) Marion von Osten -- Action research : generative curatorial practice Kate Fowle -- Home works Sidsel Nelund -- Evolving archive : Asia Art Archive Hyunjoo Byeon -- In the time of trying : If I Can't Dance, I Don't Want To Be Part of Your Revolution Vivian Ziherl -- Drafts, acts and lapses : Eastside Projects Chris Fite-Wassilak -- Our own bubbles of ignorance : the aesthetic of research of some biennales Carson Chan & Joanna Warsza -- Curatorial dictionary : unpacking the oxymoron tranzit.hu